Peningkatan Kualitas Kemeja Menggunakan Metode Statistical Process Control (SPC) - Nanda Isnan Pauji; Nugraha; Dewi Shofi Mulyati (UNISBA Press, 2024)
Abstract. PT Traco Global System is capable of producing 18,000 pcs per month with a daily production of 750 pcs of shirts. Defective products were discovered during the finished product inspection process which resulted in the company's targets not being achieved. There are three types of defects in shirts, namely stitching defects, shape defects, and material defects. Based on the data available, the percentage of defective shirt products that can be repaired will reach 13.70% in November 2022, which exceeds the company's defect standards. The total additional working hours of 23 hours/month resulted from the number of defective products per month divided by the average production per hour in November 2022. This problem requires methods and tools to reduce defects. The method used is Statistical Process Control (SPC), this method is used to ensure that all processes meet standards and the company can find out, analyze and reduce process errors in order to find out the causes of these errors with the tools used, namely Pareto diagrams, p control charts, and cause-effect diagrams. As well as the implementation of 5W+1H for proposed improvements to problems that occur. Based on the results of data processing on the p control chart, there are four data that are out of the upper control limit and the lower control limit, this indicates that there is a process incompatibility, causing frequent defects. Proposed improvements that must be made at each work station include creating a supervision form, conducting routine training, creating machine maintenance checksheets, improving production room construction, creating visual displays so that operators maintain safety by using personal protective equipment and cleanliness on the production floor as well as evaluating vendors on a regular basis periodically. Abstrak. PT Traco Global System mampu memproduksi sebanyak 18.000 pcs per bulan dengan capaian produksi per hari sebanyak 750 pcs kemeja. Produk cacat ditemukan pada saat proses pemeriksaan produk jadi yang mengakibatkan target perusahaan tidak dapat tercapai. Terdapat tiga jenis kecacatan pada kemeja yaitu cacat jahitan, cacat bentuk, dan cacat bahan. Berdasarkan data yang telah didapat, persentase produk kemeja cacat yang dapat diperbaiki mencapai 13,70% pada bulan November 2022, dimana melebihi standar kecacatan perusahaan. Total penambahan jam kerja sebanyak 23 jam/bulan dihasilkan dari jumlah produk cacat per bulan dibagi dengan rata-rata produksi per jam pada bulan November 2022. Permasalahan tersebut perlu metode dan tools untuk mengurangi kecacatan. Metode yang digunakan yaitu Statistical Process Control (SPC), metode ini digunakan untuk memastikan semua proses telah memenuhi standar dan perusahaan dapat mengetahui, menganalisis, serta mengurangi kesalahan proses agar dapat mengetahui penyebab terjadinya kesalahan tersebut dengan tools yang dipakai yaitu diagram Pareto, peta kendali p, dan diagram sebab-akibat (cause-effect diagram) serta penerapan 5W+1H untuk usulan perbaikan terhadap permasalahan yang terjadi. Berdasarkan hasil pengolahan data peta kendali p bahwa terdapat empat data yang keluar dari batas kendali atas dan batas kendali bawah, ini menandakan bahwa terdapat ketidaksesuaian proses sehingga menyebabkan sering terjadi kecacatan. Usulan perbaikan yang harus dilakukan pada setiap stasiun kerja yaitu membuat form pengawasan, melakukan pelatihan rutin, membuat checksheet maintenance mesin, perbaikan konstruksi ruang produksi, membuat visual display agar operator tetap menjaga keamanan dengan menggunakan alat pelindung diri dan kebersihan di lantai produksi serta evaluasi vendor secara berkala.